USING OF REFRACTORY MATERIALS, HAVING BEEN USED IN REFRACTORY FACING OF HEAT AGGREGATES ESPTS-1, 2 AT RUP “BMZ” - V. S. Pishikin; A. I. Nosovets; V. M. Nosovets; V. V. Bitjukov (Литьë и металлургия)
The workshop on processing of refractory materials is created at RUP ''BMZ'' with the purpose of increase of steal cost. The works on improvement of service characteristics of refractory production are carried out.